Interdependensi Kompleks Korea Selatan-Korea Utara dalam Sunshine Policy di Era Moon Jae-in (2017-2022) - Bandoro, Antares; Lanti, Irman (Jurnal Studi Diplomasi dan Keamanan, 2026)
The Korean Peninsula has long experienced fluctuating dynamics between South Korea and North Korea. In responding to this situation, Moon Jae-in implemented the Sunshine Policy towards North Korea. This study employs a descriptive qualitative approach using Keohane and Nye’s Complex Interdependence framework. It examines the extent to which complex interdependence was reflected in the implementation of the Sunshine Policy during the Moon Jae-in era through document analysis and literature study. The result shows that Moon Jae-in’s Sunshine Policy was on the right track to fostering complex interdependence with North Korea. However, Moon ultimately failed to sustain this effort because inter-Korean relations remained heavily dominated by state actors, political security issues, and due to the collapse of the US-North Korea summit in Hanoi, which derailed various planned inter-Korean cooperation initiatives. Keyword: Complex interdependence, North Korea, South Korea, Sunshine Policy